Інституційні умови розвитку системи економічних розслідувань на підприємствах - Мисник, К.П. (Вісник економічної науки України, 2020)
На даний час виникає необхідність пошуку нових механізмів проведення економічних розслідувань у сфері господарської діяльності підприємств і впровадження дієвих методів контролю, що дає змогу значно знизити ризики вчинення фінансових та економічних злочинів.
Мета даного дослідження полягає в обґрунтуванні й розробленні пропозицій щодо створення належних інституційних умов розвитку системи економічних розслідувань на підприємствах. Для досягнення поставленої мети використано методи аналізу і синтезу, порівняння, узагальнення, статистичного аналізу, експертного опитування, структурно-логічного аналізу.
У статті проаналізовано й узагальнено наукові підходи до визначення сутності й змісту поняття «форензік». На підставі експертних опитувань міжнародних компаній визначено особливості форензіку як методу економічних розслідувань на підприємствах України. Виконано статистичний аналіз основних показників адміністративних правопорушень в Україні. Надано пропозиції щодо створення належних інституційних умов розвитку системи економічних розслідувань на підприємствах. В настоящее время возникает необходимость поиска новых механизмов проведения экономических расследований в сфере хозяйственной деятельности предприятий и внедрения действенных методов контроля, что позволяет значительно снизить риски совершения финансовых и экономических преступлений.
Цель данного исследования заключается в обосновании и разработке предложений по созданию надлежащих институциональных условий развития системы экономических расследований на предприятиях. Для достижения поставленной цели использованы методы анализа и синтеза, сравнения, обобщения, статистического анализа, экспертного опроса, структурно-логического анализа.
В статье проанализированы и обобщены научные подходы к определению сущности и содержанию понятия «форензик». На основании экспертных опросов международных компаний определены особенности форензика как метода экономических расследований на предприятиях Украины. Выполнен статистический анализ основных показателей административных правонарушений в Украине. Даны предложения по созданию надлежащих институциональных условий развития системы экономических расследований на предприятиях. At present, there is a need to find new mechanisms for conducting economic investigations in the field of economic activity of enterprises and the introduction of effective methods of control, which can significantly reduce the risk of financial and economic crimes.
The purpose of this study is to substantiate and develop proposals for the creation of appropriate institutional conditions for the development of the system of economic investigations in enterprises. To achieve this goal, methods of analysis and synthesis, comparison, generalization, statistical analysis, expert survey, structural and logical analysis were used.
The article analyzes and generalizes scientific approaches to defining the essence and content of the concept of "forensic". On the basis of expert surveys of international companies, the peculiarities of forensics as a method of economic investigations at Ukrainian enterprises have been identified. A statistical analysis of the main indicators of administrative offenses in Ukraine has been performed.
To ensure the development of the system of economic investigations at enterprises, it is proposed to create appropriate institutional conditions, namely:
at the legislative level to define the essence of the concept of "forensics as a method of economic investigations in the field of economic activity", its principles, features, legal, organizational and financial principles of regulating development in enterprises;
to form an appropriate institutional environment, i.e institutions that would control and regulate the process of economic investigations. For example, legislative work is currently under way to establish the Bureau of Financial Investigations as the central executive body that implements state policy to prevent, detect, stop, investigate and detect criminal offenses in the field of economic activity that directly or indirectly harm the public interest. in the field of finance. That is, it is planned to create a single body in which to investigate all economic crimes against the state;
to form an integrated structure of interaction between financial institutions and central executive bodies for the organization of forensics at enterprises of various types of economic activity and organizational and legal forms of ownership;
to develop an organizational and economic mechanism for managing the development of the system of economic investigations at enterprises;
to develop the mechanism of information support of development of system of economic investigations at the enterprises with use of digital technologies.